2019
DOI: 10.1097/inf.0000000000002267
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Lactobacillus Reuteri DSM 17938 in Healthy Children 2–5 Years of Age

Abstract: Probiotics are increasingly used for diarrhea, but studies under the Food and Drug Administration and Investigational New Drug program are few. We conducted a phase-one placebo-controlled study of Lactobacillus reuteri DSM 17938 under Investigational New Drug program in 60 children 2–5 years of age (41 L. reuteri, 19 placebos) in a resource-constrained community in Peru. No differences in objective data on adverse events were noted, although some differences based on subjective parental reports for fever and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…L. reuteri DSM 17938 isolated from human breast milk has been characterised and administered to infants with positive outcomes reported. Kosek et al reported no safety concerns when administered to two to five year old infants [275]. Studies have concluded it is effective and have recommended its use for infants with colic [276,277].…”
Section: Probiotic Bacteria In Breast Milkmentioning
confidence: 99%
“…L. reuteri DSM 17938 isolated from human breast milk has been characterised and administered to infants with positive outcomes reported. Kosek et al reported no safety concerns when administered to two to five year old infants [275]. Studies have concluded it is effective and have recommended its use for infants with colic [276,277].…”
Section: Probiotic Bacteria In Breast Milkmentioning
confidence: 99%
“…They include the induction of bacterial translocation, bacteremia, sepsis, bacterial dysbiosis and the conferral of bacterial resistance genes, further complicated by the development of systemic health problems induced by these conditions (30). Cumulative evidence from the literature nevertheless, proves an overall excellent safety record for the long-term consumption of probiotics by healthy adults and children (31)(32)(33). There are however various case reports of bacteremia, fungemia or bacterial dysbiosis or other adverse events.…”
Section: Safety Aspects Of Probiotics Consumptionmentioning
confidence: 99%